Portrait of Junior High School Teachers' Readiness for Deep Learning in The Independent Curriculum in Makassar City - Mislia; Juhari, Agusalim; Asmayani (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to portray the readiness of junior high school teachers in Makassar City to implement deep learning within the Merdeka Curriculum and to identify the strongest and weakest dimensions of their readiness. The research employed a descriptive quantitative approach with a cross-sectional design, involving approximately 70 teachers from three representative schools selected through proportional random sampling. The instrument used was a five-point Likert questionnaire covering five dimensions of readiness: conceptual understanding, lesson planning, classroom implementation, attitude and motivation, and environmental support. The findings revealed an overall mean readiness score of 3.62, which falls into the “ready” category, with 12% of teachers categorized as very ready, 58% ready, 26% moderately ready, and 4% less ready. The strongest dimension was attitude and motivation (mean 4.02), while the weakest dimensions were environmental support (3.35) and classroom implementation (3.41). These results highlight the need for stronger institutional support, adequate facilities, and practical mentoring to ensure that deep learning can be effectively and sustainably implemented in schools.